Government responses to gender-based violence during COVID-19 - Rebecca Gordon; Nic Cheeseman; Sarah Rockowitz; Laura M. Stevens; Heather D. Flowe (Frontiers Media S.A., 2022)
Gender-based violence (GBV) significantly and substantially threatens women's health. The COVID-19 pandemic has exacerbated existing risks and patterns of GBV. The impact of COVID-19 on GBV is not inevitable, however, and can be mediated by the policies of governments. In this study we developed the Government GBV Response Index to systematically examine how countries (N = 60) performed in response to the pandemic with respect to the government 1) enacting specific national-level GBV policy; 2) making dedicated COVID-19 specific funding available; and 3) adapting existing GBV responses to COVID-19 related restrictions and challenges. Most countries (N = 33) delivered fewer than two policy responses. We also performed rapid case study analyses to investigate what might contribute to countries having more comprehensive government policy. We find that civil society organizations played a key role in facilitating GBV policy during the pandemic, especially if they are well-funded and well-connected to the government, and if the country has a high-level government official responsible for gender issues.